2008
DOI: 10.1055/s-2008-1073153
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and Autoimmune Thyroid Diseases

Abstract: Chemokines are a family of small, structurally related molecules that regulate cell trafficking of various types of leukocytes through interactions with their seven-transmembrane, G protein-coupled receptors. Their major function is the recruitment of leukocytes to inflammation sites, but they also play roles in tumor growth, angiogenesis, organ sclerosis, and autoimmunity. A variety of evidence has accumulated to support the concept that thyroid follicular cells as well as intrathyroidal lymphocytes are able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 38 publications
0
34
0
2
Order By: Relevance
“…Their serum levels vary during the course of AIT because of the causes like disease duration and activity, thyroid function status and pharmacological treatment [16]. Though past research focused on the expression of several chemokines in thyroids of patients with AIT, possible role of chemokines has been less extensively studied in sera of patients [5,17]. In 2004, Antonelli et al [18] reported that circulating CXCL10 was increased in patients with AIT and is associated with chronic autoimmune thyroiditis and hypothyroidism and may be regarded as a marker of a more aggressive thyroiditis leading to thyroid destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Their serum levels vary during the course of AIT because of the causes like disease duration and activity, thyroid function status and pharmacological treatment [16]. Though past research focused on the expression of several chemokines in thyroids of patients with AIT, possible role of chemokines has been less extensively studied in sera of patients [5,17]. In 2004, Antonelli et al [18] reported that circulating CXCL10 was increased in patients with AIT and is associated with chronic autoimmune thyroiditis and hypothyroidism and may be regarded as a marker of a more aggressive thyroiditis leading to thyroid destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the clinical manifestations of glandular GD are predictable and can be treated with relative ease in the vast majority of patients 86. A detailed description of the endocrine derangements associated with GD is beyond the scope of this article, and can be found elsewhere 47,77,105…”
Section: Immunology Of Gdmentioning
confidence: 99%
“…In a typical scenario, after IFN-g stimulation, several endocrine cells secrete CXCL10, which in turn recruits Th1 lymphocytes that express CXCR-3 and secrete IFN-g, establishing an important loop for the sustainment of inflammatory reactions [1]. Accordingly, the CXCR-3-binding chemokines have also been proven to play pivotal pathogenic roles in both human studies and mouse models for autoimmune thyroid diseases (AITD) [3].…”
Section: Introductionmentioning
confidence: 98%